Major QTLs, qARO1 and qARO9, Additively Regulate Adaxial Leaf Rolling in Rice - Jang, Su; Shim, Sangrea; Lee, Yoon Kyung; Lee, Dongryung; Koh, Hee-Jong (Frontiers in Plant Science, 2021)
Moderate leaf rolling is considered optimal for the ideal plant type in rice (Oryza sativa L.), as it improves photosynthetic efficiency and consequently grain yield. Determining the genetic basis of leaf rolling via the identification of quantitative trait loci (QTLs) could facilitate the development of high-yielding varieties. In this study, we identified three stable rice QTLs, qARO1, qARO5, and qARO9, which control adaxial leaf rolling in a recombinant inbred line (RIL) population derived from a cross between Tong 88-7 (T887) and Milyang 23 (M23), using high-density SNP markers. These QTLs control the rolling phenotype of both the flag leaf and secondary leaf, and different allelic combinations of these QTLs lead to a wide variation in the degree of leaf rolling. Additive gene actions of qARO1 and qARO9 on leaf rolling were observed in a backcross population. In addition, qARO1 (markers: 01id4854718 and 01asp4916781) and qARO9 (markers: 09id19650402 and 09id19740436) were successfully fine-mapped to approximately 60 and 90 kb intervals on chromosomes 1 and 9, respectively. Histological analysis of near-isogenic lines (NILs) revealed that qARO1 influences leaf thickness across the small vein, and qARO9 affects leaf thickness in the entire leaf and bulliform cell area, thus leading to adaxial leaf rolling. The results of this study advance our understanding of the genetic and molecular bases of adaxial leaf rolling, and this information can be used for the development of rice varieties with the ideal plant type.